Structural optimisation of lactic acid derivatives to obtain enhanced ferroelectric properties in smectic phases. Issue 1 (2nd January 2023) - Podoliak, Natalia; Novotná, Vladimíra; Hamplová, Věra; Pociecha, Damian; Cigl, Martin
ABSTRACT: Ferroelectricity is a desirable property of liquid crystalline materials. To enhance the ferroelectric properties, we optimised the molecular structure of the previously synthesised compounds DLm/n and prepared a series of ( S )-lactate mesogens denoted ZL, which differ in a linkage of the non-chiral chain by an additional ether group. By this modification, we have succeeded in broadening the temperature range of a ferroelectric SmC* phase and spreading it down to room temperature, as well as in decreasing the melting points in comparison with the previously studied compounds. Also, the spontaneous electric polarisation of ZL compounds was found to be higher than that of parent mesogens. GRAPHICAL ABSTRACT: uf0001